Psyco-Social Environment Analysis dalam kebijakan ruang terbuka hijau (RTH) di kawasan perkotaan Indonesia - Dwiana Inggriani; Zulkarnain Zulkarnain; Viktor Amrifo (Pelantar Press, 2020)
This research was carried out in Oktober – November 2019 at Jadirejo Village, Sukajadi Village, Umban Sari Village and Rumbai Bukit Village. The purpose of this study is to analyze the community’s understanding of green open space green as part of environmental management in Pekanbaru City, analyze people’s view about green open space to protect the environment and analyze the community’s assessment of green open space existence to protect the living environment. Research approach used is descriptive quantitative with proportional random sampling technique using a questionnaire as instrument. The data obtained were processed using the Skala Liker’s. The results of this study are the community perception about green open space in Pekanbaru City was considered good, the level of respondent’s understanding are good category, majority of respondent’s views are in high category, majority of respondent’s assessment of green open space are not good enough category, and the location of residence doesn’t affect to community’s perception of green open space.